Stirred but not shaken: population and recruitment genetics of the scallop (Pecten fumatus) in Bass Strait, Australia. (8th May 2016) - Ovenden, Jennifer R.; Tillett, Bree J.; Macbeth, Michael; Broderick, Damien; Filardo, Fiona; Street, Raewyn; Tracey, Sean R.; Semmens, Jayson
Abstract: We report population genetic structure and fine-scale recruitment processes for the scallop beds ( Pecten fumatus ) in Bass Strait and the eastern coastline of Tasmania in southern Australia. Conventional population pairwise FST analyses are compared with novel discriminant analysis of principal components (DAPC) to assess population genetic structure using allelic variation in 11 microsatellite loci. Fine-scale population connectivity was compared with oceanic features of the sampled area. Disjunct scallop beds were genetically distinct, but there was little population genetic structure between beds connected by tides and oceanic currents. To identify recruitment patterns among and within beds, pedigree analyses determined the distribution of parent–offspring and sibling relationships in the sampled populations. Beds in northeastern Bass Strait were genetically distinct to adjacent beds ( FST 0.003–0.005) and may not contribute to wider recruitment based on biophysical models of larval movement. Unfortunately, pedigree analyses lacked power to further dissect fine-scale recruitment processes including self-recruitment. Our results support the management of disjunct populations as separate stocks and the protection of source populations among open water beds. The application of DAPC and parentage analyses in the current study provided valuable insight into their potential power to determine population connectivity in marine species with larval dispersal.